Oneness Embraced - Evans, Tony (Chicago Moody Publishing, 2011)
"Black/white relations in the culture at large and in the church in particular continue to be a stain on America's respectable reputation. The church has clearly failed and must seek to function by God's kingdom perspective. In this legacy message, Tony
Keywords: Race relations -- Religious aspects -- Christianity. United States -- Race relations. African Americans -- Religion